Studi Karakteristik Pengaruh Kekasaran Permukaan Terhadap Hasil Sambungan Las Spot Welding Pada Material Aluminium Paduan - Hanggoro, Nurbiasto, Muh. Alfatih Hendrawan, ST, MT, Joko Sedyono, ST, MT, Ph.D (2015)
Spot welding is a welding method that uses electric resistance (Resistance Welding) wherein two plate surfaces to be joined pressed to each other by two electrodes. Aluminum is very easy to react with water and air, if the aluminum reacts with water and air, it forms a layer of oxide (Al2O3) on the surface of aluminum. This oxide layer will lead to aluminum is difficult to weld. Engineering process surface roughness difference in the aluminum layer will reduce the thickness of the oxide layer. This study aims to determine the effect of surface roughness on the physical and mechanical properties in the weld. This study uses aluminum alloy with a thickness of 1 mm. Variation of parameters used in this study is the welding current 7000 A, 8000 A, 9000 A, and the welding time of 0.5 seconds, 0.6 seconds, 0.7 seconds and process engineering difference of surface roughness using sandpaper (2.796 to 2.911 m) , sandblasting (5.229 to 5.338 m), and grinding (8.569 to 9.229 m). Chemical composition testing using ASTM standard 1251, shear strength test specimens using standard ASME IX, macro and micro testing picture using ASTM standard ASTM E3 and E7. The results showed that the study material is aluminum alloy Zn (Al 98.18% - 0.737% Zn) approached the 7000 series variation of flow parameters, time, and the surface roughness affects the yield strength of welded joints. The greater the current, time, and the rough surface will increase the strength of the weld joint results. The smallest nugget width is 0.759 mm occurred in the current 7000 A, a time of 0.5 seconds, and the surface roughness of sandpaper. While the width of the biggest nugget is 2.02 mm occurs in the current 9000 A, time 0.7 seconds, and the surface roughness using sandblasting and grinding. The images showed that the size of the largest micro-grain structure of the metal contained in the current 9000 A, 0.7 times, and the surface roughness using a grinder. Keywords: Spot Welding, Aluminum Alloys, Surface Roughness, Tensile Strength , Metallography